THE TERMINATION OF KNOWN CONTRACTS IN CIVIL CODE AND THE CASES OUT OF THE CIVIL CODE OF IRAN - Amir Vahidi Nezhad, Issa Alijanpour (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
A contract is a legal phenomenon, the enforcement of the provisions of which is terminated usually by acting based on the undertaking. The termination of a contract is dependent on the subject and various causes, and cancelation and dissolution are clear examples of that. For example, in article 344 of the Civil Code of Iran, the sanction of enforcing lack of appointing the time limit of submission and lack of mentioning the contractual conditions can make the sale definite, and the time limit is assigned to an arbitration court in some cases. Time fixing has various aspects and effects in different contracts. In some cases, the parties can’t or refuse to fix the contract time at the time of the establishment of the contract for any reason, which is called an open contract. This is against the basic conditions of the establishment of a contract and is doomed to cancellation. On the other hand, such contracts are today recognized. Besides, in the enforcement step of a contract, time fixing is vital, and in case of expiration of the agreed period and preparation of terms of the claim, the committed party is charged to enforce the contractual provisions. In general, the principle is one the emergency of the fulfillment of undertakings; although the parties can fix a time to enforce the contract. Hence, the beginning and signature time of the contract should be specified, because it can be effective in terms of effects of the contract, the possibility of claiming for compensation, or fulfillment of undertakings. In this study, the contract period (from the time of establishment to the termination of contract) is evaluated regarding its effects.